Control potential of multiple nucleopolyhedrovirus (SfMNPV) isolated from fall armyworm in Nigeria (West Africa) - Tepa-Yotto, G.; Douro Kpindou, O.; Koussihouede, P. S.; Adjaoke, A.; Winsou, J. K.; Tognigban, G.; Tamò, Manuele (MDPI, 2024)
The fall armyworm (FAW) Spodoptera frugiperda (Lepidoptera, Noctuidae) has now become an invasive pest of global concern. The pest was first detected in Central and Western Africa in early 2016. Sustainable management options explored by stakeholders during early FAW invasion in Africa included the use of biopesticides and biological control. The current study aimed to compare the susceptibility of FAW larvae to SfMNPV with the assumption that the virus isolated from FAW populations in Africa has higher virulence compared with an isolate from Argentina (SfMNPV-ARG). We also hypothesized that host plant plays a role in SfMNPV efficacy and that cannibalism mediates horizontal and vertical transmission of the virus. This work provides pioneering data on the virulence of the new SfMNPV isolate from Nigeria (SfMNPV-KA1), which proved more effective than its exotic counterpart from Argentina (SfMNPV-ARG). The host plant effect made a significant difference between maize and onion with more FAW death in the larvae fed with contaminated onion 5 days post treatment. The study demonstrates and discusses the effect of cannibalism on virus transmission.